Cadmium ion adsorption properties of polyanions carrying carboxylate and thiol-containing amino acid residues - Nakahata, Masaki; Okamoto, Chikano; Tanaka, Motomu; Hashidzume, Akihito (ACS applied polymer materials, 2025)
Access to clean water is important for a sustainable society. To reach this goal, various materials, including zeolites and ion exchange resins, have been used to remove harmful heavy metal ions from water. However, the affinity, selectivity, and loading capacity of these materials are limited because ions are recognized according to their size and valency. To increase the affinity and loading capacity for heavy metal ions such as Cd2+, we designed and prepared a series of copolymers carrying carboxylic acid and thiol groups. These copolymers mimic the structure of heavy metal-binding proteins. The copolymers were prepared using N-acryloylcysteine and an anionic comonomer (acrylic acid, N-acryloylglycine, N-acryloylaspartic acid, or N-acryloylglutamic acid) and were characterized by 1H NMR spectroscopy and size exclusion chromatography. The interactions of these copolymers with Cd2+ were investigated using a colorimetric assay, dynamic light scattering, and isothermal titration calorimetry. The colorimetric assay demonstrated that the removal capacities of the copolymers for Cd2+ met the World Health Organization standard for drinking water. Notably, after neutralizing the copolymers with sodium hydroxide, their ion loading capacities improved. The loading capacities of the copolymers were comparable to or higher than those for other inorganic, organic, biobased, and hybrid materials reported to date. The findings of this study can improve the Cd2+ loading capacity by fine-tuning the copolymer structures, including charge, counterion, and composition.
Online veröffentlicht: 5. Juni 2025
Gesehen am 15.09.2025